Muscle strength imbalance between hamstring and quadriceps among professional dancers (Bioscience Journal, 2016)
The aim of this study was to evaluate the unilateral strength in knee flexion and extension, and the Hamstring/Quadriceps Ratio (H/Q Ratio), in dominant and non-dominant lower limbs in professional dancers. This was a cross-sectional study, carried out with 12 health adults (27.5±1.27years, 66.6±3.11kg, 173±0.02cm, 22.1±0.51kg/m2), professional dancers of a national company. The volunteers, after physical measurements, were submitted to a 1 Repetition Maximum (1RM) test, unilaterally, in both lower limbs at Flexor and Extensor Bench seat exercises. After 1 week, a 1RM retest was carried out to confirm the real total load for each limb. The torque and H/Q Ratio were calculated unilaterally. In knee extension, the dominant limb presented strength 18.77% higher than non-dominant limb (p